Male occult breast cancer with features highly resembling primary lung cancer: a case report and literature review - Su, Hao; Zhao, Xinyu; Liu, Huayu; Shu, Huantong; Li, Wenjing; Yang, Zhimin; Li, Mianli (Frontiers in Oncology, 2026)
Male breast cancer is an extremely rare form of malignant tumor, and occult breast cancer is also an exceptionally uncommon disease. Given its rarity, diagnosing occult breast cancer in male patients presents significant challenges, and the diagnosis becomes even more difficult when the tumor exhibits characteristics of other neoplasms. For instance, this case report describes a male patient with occult breast cancer presenting with features typical of primary lung cancer. The uniqueness and complexity of this case lie in its clinical presentation: beyond typical axillary lymph node enlargement, the primary imaging feature was an isolated pulmonary mass lesion. This presented significant diagnostic hurdles. For the diagnosis of this case, we administered chemotherapy and intracranial radiotherapy to the patient. Therefore, sharing this rare case aims to heighten clinicians’ awareness of differential diagnoses for metastatic cancer with an unknown primary site, particularly when pathological findings of pulmonary lesions do not align with conventional lung cancer markers.